(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract. The concept of linked data emphasizes on Global data space which inherently holds embedded semantic relations based on various mapping approaches. Text based search has least relevance as compared to semantically enabled searching and recommendations. Tourism is ever-growing domain for recommendation and suggestions. This paper proposes an approach which makes use of semantically enabled context for the point of interest and tourist preferences as well. There are several contexts (e.g. user’s companion, duration of trip, budget) which has dominant effect on the overall outcome of the search. Recommender system is used to suggest the user for optimized preferences based on ranking. However this recommendation could be increased manifold if the semantic based concept of context is mapped in these algorithms. Contexts are inherently imprecise because of similar meaning sense. Probabilistic mapping could be used to filter these contexts. The proposed approach in this paper is to make use of semantic context for places which could be mapped with the filtered contexts and thereafter based on user’s preferences. This work focuses on existing recommendations algorithm along with proposed ontology and mapping approach to make better recommendation system.